The evolution of hospitals from Antiquity to the Renaissance - Francois P. Retief; Louise Cilliers (Acta Theologica)
There is some evidence that a kind of hospital already existed towards the end of the 2nd millennium BC in ancient Mesopotamia. In India the monastic system created by the Buddhist religion led to institutionalised health care facilities as early as the 5th century BC, and with the spread of Buddhism to the east, nursing facilities, the nature and function of which are not known to us, also appeared in Sri Lanka, China and South East Asia. One would expect to find the origin of the hospital in the modern sense of the word in Greece, the birthplace of rational medicine in the 4th century BC, but the Hippocratic doctors paid house-calls, and the temples of Asclepius were visited for incubation sleep and magico-religious treatment. In Roman times the military and slave hospitals were built for a specialised group and not for the public, and were therefore not precursors of the modern hospital. It is to the Christians that one must turn for the origin of the modern hospital. Hospices, originally called xenodochia, initially built to shelter pilgrims and messengers between various bishops, were under Christian control developed into hospitals in the modern sense of the word. In Rome itself, the first hospital was built in the 4th century AD by a wealthy penitent widow, Fabiola. In the early Middle Ages (6th to 10th century), under the influence of the Benedictine Order, an infirmary became an established part of every monastery. During the late Middle Ages (beyond the 10th century) monastic infirmaries continued to expand, but public hospitals were also opened, financed by city authorities, the church and private sources. Specialised institutions like leper houses also originated at this time. During the Golden Age of Islam the Muslim world was clearly more advanced than its Christian counterpart with regard to the magnificent hospitals which were built in various countries, institutions which eventually became the true forerunners of the modern teaching hospital.